How to Have Creative Ideas
Everybody wants to be creative. Creativity makes life more fun, more interesting and more full of achievement, but too many people believe that creativity is something you are born with and cannot be learned. In How to Have Creative Ideas Edward de Bono - the leading authority on creative thinking - outlines 62 different games and exercises, built around random words chosen from a list, to help encourage creativity and lateral thinking. For example, if the task were to provide an idea for a new restaurant and the random word chosen was 'cloak', ideas generated might be: a highwayman theme; a Venetian theme with gondolas; masked waiters and waitresses. Or, if asked to make a connection between the two random words 'desk' and 'shorts', readers may come up with: both are functional; desks have 'knee holes' and shorts expose the knees; traditionally they were both male-associated items. All the exercises are simple, practical and fun, and can be done by anyone.Bestselling author Edward de Bono presents 62 practical exercises to encourage creativity and lateral thinking